Conflicting forces in the implementation of medicinal cannabis regulation in Uruguay - Eliana Alvarez; Rosario Queirolo; Belen Sotto (BMC, 2023)
Abstract Background Uruguay is widely known as a pioneer country regarding cannabis regulation policies, as it was the first state to regulate the cannabis market for both recreational and medicinal purposes in 2013. However, not all aspects of the regulation have moved forward at the same speed. Medicinal uses keep facing several challenges that undermine patients' effective access to treatments and products. What are those persistent challenges for the medicinal cannabis policy in Uruguay? This paper aims to describe and understand the current state of medicinal cannabis in the country and identify the most critical challenges and conflicting forces for its proper implementation. Methods To do so, we conduct twelve in-depth interviews with key informants, including governments officials, activists, entrepreneurs, researchers, and doctors. These interviews are complemented with information from the congressional committees' public records and other documentary sources. Results This research shows that the legal framework was thought to assure quality products over access. The main challenges of medicinal cannabis in Uruguay are related to three issues: (i) the timid development of the industry, (ii) a limited and expensive supply, and (iii) the emergence of an informal productive sector. Conclusions The political decisions regarding medicinal cannabis made in the last seven years have derived from a halfway policy that fails to guarantee patient access or promote the growth of a vibrant national industry. Positively, the several actors involved are aware of the extent of these challenges and new decisions have been made to overcome them, meaning that monitoring the future of the policy is very much needed.